2017
DOI: 10.4049/jimmunol.1700706
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanoparticles Inhibit the Antimicrobial Activities of the Human Cathelicidin LL-37 through Structural Alteration

Abstract: Host defense peptides, also known as antimicrobial peptides, are key elements of innate host defense. One host defense peptide with well-characterized antimicrobial activity is the human cathelicidin, LL-37. LL-37 has been shown to be upregulated at sites of infection and inflammation and is regarded as one of the primary innate defense molecules against bacterial and viral infection. Human exposure to combustion-derived or engineered nanoparticles is of increasing concern, and the implications of nanomaterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The ability of LL-37 to directly inhibit a number of viruses has been reviewed previously (Barlow et al, 2014b), with further activities found against Aichi virus A (Vilas Boas et al, 2017), human adenoviruses 8 and 19 (HAdV-8 and HAdV-19) (Gordon et al, 2005; Uchio et al, 2013), hepatitis C virus (HCV) (Matsumura et al, 2016), human papillomavirus 16 (HPV16) (Buck et al, 2006), human rhinovirus (HRV) (Findlay et al, 2017; Schögler et al, 2016; Sousa et al, 2017), and varicella zoster virus (VZV) (Crack et al, 2012). While LL-37 has only been measured at 0.5 μg/ml in saliva (Bachrach et al, 2006; Takeuchi et al, 2012) and 10 μg/ml in gingival crevicular fluid 29 , the actual physiological concentration may be much higher at sites closer to the oral epithelial cells themselves due to the diffusion of the peptides once released from cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of LL-37 to directly inhibit a number of viruses has been reviewed previously (Barlow et al, 2014b), with further activities found against Aichi virus A (Vilas Boas et al, 2017), human adenoviruses 8 and 19 (HAdV-8 and HAdV-19) (Gordon et al, 2005; Uchio et al, 2013), hepatitis C virus (HCV) (Matsumura et al, 2016), human papillomavirus 16 (HPV16) (Buck et al, 2006), human rhinovirus (HRV) (Findlay et al, 2017; Schögler et al, 2016; Sousa et al, 2017), and varicella zoster virus (VZV) (Crack et al, 2012). While LL-37 has only been measured at 0.5 μg/ml in saliva (Bachrach et al, 2006; Takeuchi et al, 2012) and 10 μg/ml in gingival crevicular fluid 29 , the actual physiological concentration may be much higher at sites closer to the oral epithelial cells themselves due to the diffusion of the peptides once released from cells.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of titanium oxide nanoparticles or liposomes inhibited lymphocyte- and macrophage-related immune responses and increased susceptibility to tumor growth ( 117 , 129 ). Augmented viral and bacterial infections have also been observed after exposure to carbon nanoparticles ( 130 , 131 ).…”
Section: Nanoparticles Induce Immunosuppressionmentioning
confidence: 99%
“…The process, called citrullination, involves changing the positively charged arginine in LL37 to citrulline and thus changing its charge from positive to neutral. This effectively removes the mechanism by which LL37 is able to destroy viruses and bacteria (5,33). Additionally, neutralization of charge by citrullination is responsible for disabling its ability to dampen inflammatory responses to viral infections.…”
Section: Fine Particles In Air Pollution May Interfere With Vitamin Dmentioning
confidence: 99%